Occupational therapists’ experiences in providing training to caregivers of hospitalized older adults: a way forward for occupational therapy practice - Ghafar, Isma Hanis; Kadar, Masne; Razaob, Nor Afifi; Mukahar, Rohana; Asmuri, Siti Noraini (Taylor and Francis Ltd., 2025)
Aims: This study explores the experiences of occupational therapists in training caregivers of hospitalized older adults, with the aim of identifying strategies to enhance this practice. Methods: Six occupational therapists participated. Results: Two major themes were generated: (1) challenges in providing training to caregivers and (2) ways to improve caregiver training services. Seven sub-themes were also identified. The findings highlighted several challenges regarding the provision of training to caregivers that need to be taken into consideration by occupational therapists, as well as valuable suggestions regarding the need for effective guidelines, appropriate content, and the utilization of technology to support occupational therapists in the provision of quality caregiver training services Conclusions: Integrating healthcare professionals’ experiences is vital for improving services, recognizing the need for caregiver-centric approaches, emphasizing communication improvement within healthcare teams, and advocating for deeper insights into older adults’ needs, while highlighting the importance of technology integration in caregiver training.